Clinicopathological characteristics, treatment and prognosis of phyllodes tumor in reference centers in Medellín, Colombia - Bonilla-Sepúlveda, Óscar Alejandro (2021)
Objective: To describe the sociodemographic data, clinical and paraclinical manifestations, treatment and recurrence, among a series of patients diagnosed with phyllodes tumor. Methods: Descriptive, retrospective study of an institutional database, between January 1, 2016 and December 31, 2019. Demographic, clinical and paraclinical data were collected from medical records, which were analyzed using descriptive statistics. Results: The prevalence of phyllodes tumor in the sample was 1.3%. All cases were women, mean age 42 years, with breast mass as the most frequent reason for consultation (n = 42, 97.6%), mean tumor size 8.6 cm (range 2.1-20 cm). The sharp biopsy made the diagnosis of phyllodes tumor in 8 patients (18.6%) and fibroadenoma in 30.2% (n = 12). According to the histological classification, the most frequent were the benign and borderline type with 34.9% (n = 15) each, and malignant in 30.2% (n = 13). The type of surgery most performed was quadrantectomy in 55.8% (n = 24). The mean follow-up was 60.3 months and relapse occurred in 9.3% (N = 4) in about 23.2 months. Conclusions: In the sample studied, the phyllodes tumor affected women in the fourth decade of life, it appeared as a large, unilateral mass, without predominance of laterality, of rapid growth. The optimal treatment was surgery with wide negative margins, and radiotherapy in selected cases. The risk of recurrence is important.